Determination of the kinetics of biodiesel saponification in alcoholic hydroxide solutions. (15th January 2015) - Eze, Valentine C.; Harvey, Adam P.; Phan, Anh N.
Highlights: Quantitatively investigated kinetics of fatty acid alkyl esters saponification in alcoholic hydroxides. FAME saponification occurred 5–7 times more rapidly in ethanol than in methanol. Found actual saponification rate constants for the methanol–KOH and ethanol–KOH. Found activation energies for the FAME saponification in the alcoholic hydroxides. Provided useful data in understanding/modelling base-catalysed transesterification reactions. Abstract: The research focused mainly on kinetics of the side reactions occurring during homogeneous base-catalysed transesterification processes, which were not studied previously. The rates of fatty acid methyl esters (FAME) saponification with sodium and potassium hydroxides were investigated in methanol and ethanol (commonly used in biodiesel production) at temperatures of 40, 50 and 60 °C. The effect of water on the rate of FAME saponification in the alcoholic hydroxide solutions was also studied (at 60 °C). The apparent rate constants of FAME saponification were strongly influenced by the types of alcohol, but little affected by variation of the metal hydroxides. The apparent rate constants for FAME saponification using the ethanol hydroxides were 5–7 times higher than for methanol hydroxides. This was due to the lower acidity of ethanol, leading to a higher concentration of hydroxide ions in the ethanol–hydroxide solutions. The rate constant of the FAME saponification increased with temperature. For example, it was 1.31 L mol −1 min −1 at 40 °C, but 3.08 and 5.63 L mol −1 min −1 at 50 and 60 °C in the methanol–NaOH solution. Arrhenius activation energies for the FAME saponification in the alcoholic hydroxides were in the range of 60.3–64.0 kJ mol −1 . It was found that the FAME saponification rate in ethanol–hydroxides was 3.5 times higher than that in methanol–hydroxides in the presence of water. This indicates that use of methanol should be preferred over ethanol in alkali-catalysed transesterification, as the amount of soap produced by saponification of triglycerides and alkyl esters will be lower.